Biochar from separated digestate and pig manure as soil amendment - Nissen, Lovisa (SLU/Dept. of Soil and Environment, 2022)
The situation in and around the Baltic Sea, with large areas with hypoxia in the sea and areas in the watershed with a high concentration of animal farms, has led to a need to increase the nutrient recycling of animal manure. High levels of phosphorus (P) in the soil lead to leaching, and by reducing the P-level in organic fertilizers, this leaching can be reduced. By transporting P to areas with few animal farms, farmers’ use of organic fertilizers can increase. Through the process of mechanical separation, it is possible to create a solid fraction that is rich in P and dry matter (DM). Since it has low water content, it is easy to transport it to areas with a large need of P. Screw press separation is an easy method that is cheap and that can be implemented on a large scale for separation of both manure and digestate. Screw press solids can be turned into biochar through pyrolysis because of the low water content. The use of separated material is beneficial for the carbon (C) sequestration of the soil, and biochar causes further stabilization of the material, making it even better for C storage. Several different methods can increase C in the soil with for example organic amendments or biochar. This project aimed to evaluate biochar produced from screw press separated material from digestate and pig manure with respect to C stability and nitrogen (N) release during 50 days after the incorporation in soil. Two different pyrolysis temperatures (400 and 550°C) were used to produce biochar, and the treatments were tested with and without the application of mineral N. The properties were studied in a laboratory study, where biochar and solids were incubated with soil in 15°C. Samples were removed during the incubation in order to follow the development of N, C, pH and DM. CO2-emission was measured using NaOH-traps to calculate C mineralization. Mineral-N was measured by the extraction of NH4+ and NO3- with KCl. The screw press separation of digestate resulted in 25 % of the initial P in the solid fraction and 11 % of the initial N. When processing the materials, the concentration of nutrients increased, and the stability of C increased. The addition of mineral N to the treatments incorporated into the soil resulted in lower CO2-emission. The highest emission of CO2 came from manure solids, while biochar had very low emissions. This indicates that there was a good supply of C for microorganisms to degrade in the manure solids, and that the stability of C in biochar was high. From the added C, 37 % was lost in the form of CO2 from manure solids while the biochar lost <2 % of the total amount of C. “Biochar 550” seemed to produce higher CO2-emissions, but significant differences could only be found in one biochar. There were no differences in inorganic-N levels between the biochars. An addition of N caused Net N immobilization, while the biochar without N caused mineralization. Using screw press is a good option when treating materials such as digestate and manure. There are methods that are more effective when separating P and DM but that cost more. In our study, we found that in the short term, biochar might be able to mineralize N and increase the availability to the plant, but the total amount was very low. Biochar would be a good option for organic amendments since the loss of C is much lower than for amendments from the solid material that biochar was derived from. The application rate was equivalent to 25 000 kg/ha. Other studies have seen differences in performance in the soil and on crop yield between biochars, but in this study, the biochars were very similar when looking at CO2-emissions and N mineralization. Biochar shows potential in decreased C losses compared to their corresponding solids, and the addition of mineral N has a positive effect on CO2-emission, is which are reduced.